Alterações da morfologia craniofacial e da via aérea superior em crianças com obstrução na nasofaringe - Ballista, Paula Ramos (2016)
INTRODUCTION: The replacement of nasal breathing by predominantly mouth breathing leads to changes on teeth positions and facial growth. The persistence of mouth breathing during orthodontic correction risks the treatment outcome. Therefore, the respiratory function normalization is extremely important for the orthodontic treatment stability. The professional should refer a child to the otolaryngologist (ENT) when notes in a cephalometric image (CI) a nasopharynx obstruction compatible with adenoid hypertrophy (AH). OBJECTIVE: Assess craniofacial changes and upper airway (UA) morphology in CI of children with nasopharynx obstruction compatible with AH, aiming to assist the early diagnosis of sleep-disorder breathing (SDB) in childhood. METHODS: The sample consisted of 69 CI from 05-12 years old children. 33 children (16 girls and 17 boys, mean age 8.3 years) had nasopharynx width equal or minor than 5 mm (AH group) and 36 of them (20 girls and 16 boys, mean age 8.8 years) had nasopharynx width greater than 5 mm (NA group = no adenoid). It was evaluated, in different sex and age groups (5-7, 8-9 and 10-12 years old), skeletal facial pattern, oropharynx width (tonsils), UA vertical length, UA angulation and craniocervical (cc) angulation. Data were analyzed using Student’s t-test, ANOVA, Pearson’s X2 , Tukey test, and logistics regressions, with a confidence level of P<.05. RESULTS: AH group showed vertical facial growth tendency, skeletal Class II, increased oropharynx width and vertical length; increased angulation of UA and cc. Vertical length of UA increased more significantly in AH group than in NA group. CONCLUSION: The increase of UA vertical length occurs earlier and with greater intensity in children with AH. These are significant parameters for assisting the diagnosis of SDB in childhood.